Cedrela domatifolia (Meliaceae), a new cedar record for Peru - Reynel Rodríguez, Carlos Augusto (2023)
A new record of Cedrela domatifolia W. Palacios is presented in Chanchamayo Valley, department of Junin, which adds to 11 the number of Cedrela (Meliaceae) species recorded in Peru. The most notorious vegetative character of the species are the prominent domatia in the axils of the secondary nerves of blades. At floral characters, the petals are red to fuchsia, an uncommon feature in the genus.